Definitions of blinding in randomised controlled trials of interventions published in high-impact anaesthesiology journals: a methodological study and survey of authors. Issue 4 (12th April 2020) - Penić, Antonija; Begić, Dinka; Balajić, Karolina; Kowalski, Martin; Marušić, Ana; Puljak, Livia
Abstract : Objectives: To analyse the completeness of reporting of blinding in randomised controlled trials (RCTs) of interventions in anaesthesiology, the actual blinding status of various persons associated with an RCT and trial authors' interpretation of blinding terminology related to RCTs. Methods: This was a methodological study and a cross-sectional survey. We analysed reporting related to blinding in published RCTs of interventions published in seven highly cited anaesthesiology journals from 2014 to 2016 and registered protocols in ClinicalTrials.gov. We surveyed corresponding authors of included RCTs about their definitions of blinding. The primary outcome was the number of RCTs that explicitly described who was blinded in a trial. Secondary outcomes were definitions of blinding terminology in the trials; trial authors' interpretation of blinding terminology; discrepancies in the blinding description within registered protocols and between registered protocols and publications. Results: Out of 622 analysed RCTs, 38% were not explicitly described as either open label or blinded studies and 10% did not report any information about blinding or lack of blinding. Only one manuscript fully reported the status of blinding for various individuals that may be involved with a trial. The most common descriptor was that a trial was double-blind. We found discrepant information regarding blinding in the majority of registered protocols. Even when there were no discrepancies in the registration, we found discrepancies in the reporting of blinding between the majority of registered protocols and published manuscripts. The survey of authors (40 responses from 231 eligible authors; 17% response rate) of analysed RCTs showed that they differed in how they defined different levels of blinding in trials. Conclusions: Reporting of the blinding status of key individuals involved in analysed anaesthesiology RCTs was insufficient. For reporting guidelines, peer reviewers and editors should insist on clear information on who was blinded in a trial instead of using the term 'double-blind' for different blinding practices.